The Application of the Spirit of Socio-Scientific Problem-Based Learning (SSIPBL) Model to Improve Learning Outcomes on the Respiratory System Material at Senior High School - Pratiwi, Siwi; Kusumadani, Annur Indra (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
This study aims to analyze the implementation of the SPIRIT model of problem-based biology learning (SSIPBL) on the respiratory system material at Muhammadiyah 1 Sragen High School in the 2024/2025 academic year and to determine whether this model can improve students' learning outcomes. The research type used is quantitative with an experimental design. Data collection was carried out through learning outcome tests, observations, and interviews. Based on the t-test results, a significance value (sig.) of 0.198 was obtained, which is greater than the 0.05 value, indicating that there is no significant difference between the experimental group using the SSIPBL model and the control group using conventional learning methods. Factors affecting the ineffectiveness of this model's implementation include teacher readiness, limited time, lack of student involvement, and inadequate infrastructure. The results of this study show that the implementation of the SPIRIT SSIPBL model on the respiratory system material does not significantly improve students' learning outcomes. Therefore, it is recommended to improve supporting aspects, such as teacher training, better time management, and increasing student motivation and involvement in problem-based learning. Indicates that the implementation of the SPIRIT model of Socio-Scientific Problem-Based Learning (SSIPBL) can significantly improve students' learning outcomes on the respiratory system material senior High School for the. These results suggest that SSIPBL has the potential to enhance students' understanding through a problem-based approach that connects scientific phenomena with social issues, and its implementation in the field met expectations.